(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: Osteoporosis is the most common metabolic bone disease, which is greatly reduced by lifestyle modification. The protection motivation theory (PMT) is one of the best theories to understand health behaviors and decisions made by a person to protect him or herself against harmful events and cope with them. Aims: Therefore, the researchers conducted this study to determine the effect of educational intervention based on PM theory on the osteoporosis preventive nutritional behaviors in women of reproductive age referred to healthcare centers in Sabzevar. Methods: This quasi-experimental study was performed on 66 women of the reproductive age of Sabzevar who were selected by stratified sampling. Data were collected through questionnaire, the validity and reliability of which were verified and confirmed. The intervention was held within 6 sessions. The evaluation took place three courses. The data analysis was carried out using Stata12 and p-value <0.05 was considered statistically significant Results: A total of 66 women in the reproductive age of 15-49 participated in the present study. 43% of participants were under 30 years of age. The results showed that the mean score of behavior in the experimental groups changed with time, and there was a significant difference between the two groups at different times (p≤0.0001) Conclusion: In general, the results of this study showed the positive effect of education on model constructs and eventually increasing the frequency of osteoporosis preventive nutritional behaviors in women of reproductive age. Therefore, the results support the efficacy of this model in promoting osteoporosis preventive behaviors. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.254-261